Advances of the multifaceted functions of PSTPIP2 in inflammatory diseases - Shaohui Geng; Bohan Hu; Yiwei Guan; Yijin Jiang; Zixuan Shu; Chen Li; Guangrui Huang (Frontiers in Immunology)
The complex interaction between the immune system and autoinflammatory disorders highlights the centrality of autoimmune mechanisms in the pathogenesis of autoinflammatory diseases. With the exploration of PSTPIP2, it has been discovered to play an inhibitory role in immune diseases, suggesting its potential utility in the research and treatment of rheumatic diseases. This review outlines the mechanisms of PSTPIP2 in chronic multifocal osteomyelitis (CMO), rheumatoid arthritis (RA), synovitis-acne-pustulosis-hyperostosis-osteitis (SAPHO) syndrome, liver diseases, renal diseases, pressure ulcer sepsis and diabetic obesity. The mechanisms include inhibiting the IL-1β inflammatory responses, NF-κB, ERK phosphorylation etc., promoting Erβ, and modulating the polarization of macrophage to prevent the inflammatory diseases. This review summarized current findings and offered perspectives on future research directions, laying a foundation for applying of PSTPIP2 in inflammatory diseases.